The Effect of Research-Based Learning Models Through The Photomath Application On The Mathematics Learning Outcomes Of 10th Grade Students - Gultom, Grace Amelia; Simamora, Rianita; Simarmata, Gayus (CV Putra Publisher, 2025)
This study aims to determine the Effect of the Inquiry Learning Model Through the Photomath Application on the Mathematics Learning Outcomes of Class X Br. 2 Students of State Vocational School 1 Pematangsiantar Academic Year 2025/2026. The type of research used in this study is quantitative research. In this study, the design form used is One-Shot Case Study. This research will be carried out at State Vocational School 1 Pematangsiantar, which is located at Jl. Bali No. 5, Bantan, Kec. Siantar Bar., Pematang Siantar City, North Sumatra 21142. The research implementation time is planned to last for approximately 1 month in the odd semester of the 2025/2026 academic year. Based on the results of data analysis and discussion, it can be concluded that there is a positive and significant influence of the use of the inquiry learning model through the photomath application on the mathematics learning results of class X BR 2 students of SMPK Negeri 1 Pematangsiantar in the 2025/2026 academic year. The influence is shown through the regression equation Y = 10.639 + 0.069X, with a b value = 0.069. By means of the t-test, namely thitung > ttabel (2.109 > 2.048) that it is significant and by using the coefficient of determination it can be seen that the influence is 13.7